Development and characterisation of biodegradable polymer derived from Tacca leontopetaloides starch and biochar rice husk / Ainatul Mardhiah Mohd Amin - Mohd Amin, Ainatul Mardhiah (2019)
Biodegradable polymer such as starch has the potential to be a substitute for nonbiodegradable petroleum-based polymer. Besides, starch is relatively cheap and available from a broad range of plants. In addition, the crop residue can be utilised as the feedstock, raw material or filler in the production of biodegradable polymer. In Malaysia, the major crop residue such as the generation of rice husk due to the harvesting and processing of paddy rice could be utilised as the bio-filler in biodegradable polymer. The availability of rice husk could be sustained because Malaysia is one of the prominent producers of paddy rice. Therefore, the current research has opted Tacca leontopetaloides as the base of material while biochar from rice husk was chosen as the reinforcing material to develop the biodegradable polymer which was denoted as thermoplastic starch (TPS). The objectives of this research are to develop the optimum formulation of TPS by varying the glycerol content addition with acetic acid and biochar rice husk and study its performance in chemical, morphological, mechanical and water absorption. The preparation of TPS was done through double-step processing which are solution casting and roll-milling. In chemical properties, the increment of glycerol content slightly altered the chemical structural of TPS. The morphological study showed that TPS and TPS/BCRH had smoother surface and were homogenous with increasing glycerol content. However, the increase of glycerol tended to increase the affinity of water due to the hydroscopic properties. With the addition of BCRH, TPS showed lower water uptake because the biochar had an aliphatic group that induced TPS/BCRH to be more hydrophobic. Moreover, the incorporation of BCRH also significantly improved the properties of TPS in tensile strength (TS) and elongation at break (EAB). This research also studied the biodegradability of TPS and TPS/BCRH.